PENGARUH PENYULUHAN PERPAJAKAN DAN PELAYANAN FISKUS PADA PENERIMAAN PAJAK PENGHASILAN BADAN - Nyoman Putriani, Ida Ayu; Budiartha, I Ketut (E-Jurnal Akuntansi, 2016)
Tax revenues are the main source of financing national development. How does the extension of tax and service tax authorities on corporate income tax receipts. The population under study is an effective corporate taxpayers. The study did not use all of the amount o the research object. The number of taxpayers who used a sample of 83 corporate taxpayers. Methods of data collection using questionnaires. Questionnaires data were tested with validity and reliability test. Extension of the test has been carried out taxation and service tax authorities a positive effect on corporate income tax revenue.
Keywords: Tax Counseling, Service Tax Authorities, Corporate Income Tax Revenue